Investigation of Barriers and Facilitators to Medication Adherence in Patients With Type 2 Diabetes Across Different Health Literacy Levels: An Explanatory Sequential Mixed Methods Study - Huang, Yen-Ming; Shiyanbola, Olayinka O. (Frontiers in Pharmacology, 2021)
Type 2 diabetes (T2D) incurs tremendous health costs associated with various complications due to poor blood sugar control. Medication adherence, which is correlated with patients’ health literacy, should be consistently practiced to achieve optimal control of blood sugar. A comprehensive understanding of the specific communication and psychosocial factors related to medication-taking behaviors across different levels of health literacy among people with T2D will guide the development of effective interventions and strategies to enhance medication adherence. To understand the barriers and facilitators to medication adherence in people with T2D across different health literacy levels, the Health Literacy Pathway Model was used to identify the psychosocial and communication factors that may influence medication adherence. This mixed methods study used an explanatory sequential design, including a quantitative survey followed by qualitative semi-structured interviews. Two hundred and five participants completed the survey questionnaire, and 23 participants completed semi-structured interviews. Confirmed by quantitative and qualitative data, having stronger self-efficacy and fewer concerns about medications, as well as experiencing fewer perceived barriers to medication-taking, are necessary for better medication adherence among those with low adherence. Our findings will be useful to tailor interventions for diabetes care through addressing concerns among low-adherent patients with low health literacy and emphasizing self-efficacy and perceived barriers to medication adherence among all low-adherent patients with T2D.